Effects of human disturbance on medium and large mammals in primary and secondary tropical forests in Southern Mexico - Galindo-Aguilar, Rosa Elena (2025)
Introduction: In tropical forests, populations of medium and large mammals are being impacted by human activities. Understanding how species respond to land use conversion, fragmentation, and the encroachment of roads density and settlements is of conservation interest in highly biodiverse regions. Objetive: To assess the effect of human disturbance and environmental variables on trophic guilds of medium and large mammals in the tropical forests of the Sierra Negra-Mazateca in Southern Mexico. Methods: We characterized the landscape (land use and vegetation, number of fragments, and edge density) through supervised classification of Landsat 8 images. We recorded species using camera-trap stations and evaluated the relationship between the presence and relative abundance of species with human disturbance variables using zero-inflated regression models. Results: The landscape of the Sierra Negra-Mazateca is dominated by fragments of secondary forests (48.6 %) with a small proportion of primary forests (9.6 %). We found no differences in the overall relative abundance of species between primary and secondary forests, but differences were observed for omnivore and carnivore guilds. Human disturbances had a disparate effect among guilds, negatively affecting carnivores and positively herbivores. Conclusions: Secondary forests are refuges for tolerant species. Nevertheless, we emphasize the need to conserve primary forests to safeguard medium and large mammals, especially the carnivore guild. Extensive management in secondary forests is recommended to conserve remaining primary forests, alongside community awareness and empowerment for coexistence with wildlife.